Duration of bronchoprotection of the long-acting muscarinic antagonists tiotropium & glycopyrronium against methacholine-induced bronchoconstriction in mild asthmatics. (September 2016) - Blais, Christianne M.; Davis, Beth E.; Cockcroft, Donald W.
Abstract: The duration of bronchoprotection against methacholine-induced bronchoconstriction by long-acting muscarinic antagonists (LAMA's) in asthmatics and whether these drugs differ in their pharmacodynamic properties remain to be determined. The most recent published guidelines for methacholine challenge testing (MCT) suggest that LAMA's should be abstained from for 48 h prior to testing, perhaps one week in the case of tiotropium. The objectives were to determine and compare the duration of protection of a single dose of two different LAMA's, tiotropium and glycopyrronium, against methacholine-induced bronchoconstriction. Thirteen mild-to-moderate asthmatics [with a forced expiratory volume in 1 s (FEV1 ) > 65% of predicted and a baseline methacholine provocation concentration causing a 20% reduction in FEV1 (PC20 ) ≤ 8 mg/mL] completed this double-blind, double-dummy, crossover study. Methacholine challenges were performed before treatment (5 μg tiotropium or 50 μg glycopyrronium) and at 1, 24, 48, 72, 96 and 168 h post-treatment. The minimum duration between treatment administration was 11 days. Both drugs provided significant bronchoprotection, each producing greater than a 16-fold increase in mean PC20 by 1 h. Tiotropium still provided statistically significant protection at 7 days (p = 0.0282) while glycopyrronium provided bronchoprotection until day 7 (p = 0.0590). Tiotropium provided statistically superior bronchoprotection at 24 and 72 h compared to glycopyrronium. To minimize the occurrence of false negatives, MCT guidelines should be updated to recommend a minimum one-week abstinence period from all LAMA's. MCT was also able to statistically differentiate between tiotropium and glycopyrronium with respect to the degree and duration of bronchoprotection provided by each. Clinical trial registration number:NCT02622243 . Highlights: Tiotropium provided at least 7 days of bronchoprotection against methacholine. Glycopyrronium provided up to 7 days of bronchoprotection against methacholine. Both drugs produced a 16-fold higher mean PC20 at 1 h post-treatment. Tiotropium provided statistically superior bronchoprotection at 24 and 72 h. LAMAs should be withdrawn for 7 days prior to a methacholine challenge.